Water budgeting in black tiger shrimp penaeus monodon culture using different water and feed management systems - Mohanty, R.K.; Mishra, Atmaram; Patil, D.U. (Central Fisheries Research Institute (SUMAE), 2014)
We quantify the total water use (TWU) and consumptive water use index (CWUI) in grow-out culture of Penaeus monodon at different water and feeding management protocols using the water balance equation. Under two different water management protocols, treatment-wise TWU, was 2.09 and 2.43 ha-m 122 d-1 in T1 (no water exchange) and T2 (water exchange on ‘requirement’ basis depending on water quality), respectively. The computed CWUI (m3 kg-1 biomass), was 5.35 and 6.02 in T1 and T2, respectively. Lower rates of water exchange (T2) showed significantly improved water quality, crop performance and productivity over the zero water exchange protocol. Similarly, under three different feed management protocols, treatment-wise estimated TWU was 2.52, 2.44 and 2.41 ha-m 119d-1, while the computed CWUI was 7.28, 6.88 and 6.34 in T1 (Regular feeding, 4-times a day), T2 (2-weeks feeding followed by 1-week no feed) and T3 (4-weeks feeding followed by 1-week no feed), respectively. Higher the feed input, higher was the TWU and CWUI. It was also recorded that longer the refeeding period, higher was the growth performance and yield as in the case of T3. This feeding practice also helped in lowering the feed input (7.5% in T2 and 5.5% in T3), thus minimizes the input cost and improve production efficiency.